Klasycy filozofii polskiej - Palacz, Ryszard (1935-2024) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book presents an original selection of the most important personalitites in the history of philosophy in Poland from the middle ages to the twentieth century. The contribution of each philosopher to the history of Polish and global thought was discussed against the background of their biographies and historical events. Individual chapters are devoted to the philosophers of the middle ages, the Renaissance, modern age, the Enlightenment, nineteenth century, inter- and postwar periods, who represent late scholasticism, nominalism, the Polish school of philosophy of law, humanism, Aristotelianism, religious reformatory movements, Romanticism, Hegelianism, national philosophy, philosophy of action, positivism, speculativism and metaphysicism, spiritualism, pluralism, analytical philosophy, the Lvov-Warsaw school, eclectism, phenomenology, praxeology etc.
Keywords: historia filozofii; filozofia polska; filozofowie; history of philosophy; Polish philosophy; philosophers